Rozwiązane

1. -7+6+8z-4=
2. -8x(drugich) -1-4x(drugich)+x(drugich)=
3. -5-5+3b-6=
4. -7z(drugich)+b-9b-2z(drugich) + 7=
5. 3xy - 4 + 6xy + 5x-6=
6. -8ay+7cx +5+3cy+8ay =
7. -7+8by-7ay+6+by =
8. -5ac + 8 -2by +7az - 3by =
9. -8c - 9y +6c +4 + 9y =
10. a - 5y (drugich) - 3y(drugich) - 8-6a =

Pomocy!!!



Odpowiedź :

1. -7+6+8z-4= -5 + 8z
2. -8x² -1-4x² + x²= - 13x² - 1
3. -5-5+3b-6= -16 +3b
4. -7z²+b-9b-2z² + 7= -9z² - 8b + 7
5. 3xy - 4 + 6xy + 5x-6= 9xy - 10 + 5x
6. -8ay + 7cx + 5 + 3cy + 8ay =7zx + + 5 + 3cy
7. -7+8by-7ay+6+by = - 1 +9ab - 7ay
8. -5ac + 8 -2by +7az - 3by = -5ac + 8 - 5by + 7az
9. -8c - 9y +6c +4 + 9y = -2c + 4
10. a - 5y² - 3y² - 8-6a = -5a - 8y² - 8

O to chodzi?
1. -7+6+8z-4= -11+6+8z=-5+8z
2. -8x² -1-4x²+x²= -11x²-1
3. -5-5+3b-6= -16+3b
4. -7z²+b-9b-2z² + 7= -9z²-8b+7
5. 3xy - 4 + 6xy + 5x-6= 9xy-10+5x
6. -8ay+7cx +5+3cy+8ay= 7cx+5+3cy
7. -7+8by-7ay+6+by= -1+8by²+6
8. -5ac + 8 -2by +7az - 3by= -5ac+8-5by+7az
9. -8c - 9y +6c +4 + 9y= -2c+4
10. a - 5y² - 3y² - 8-6a= -5a-8y²-8
1)-7+6+8z-4=8z-5
2)-8x(drugich) -1-4x(drugich)+x(drugich)-11x²-1
3)-5-5+3b-6=3b-16
4)-7z(drugich)+b-9b-2z(drugich) + 7=-9z²-8b+7
5)3xy - 4 + 6xy + 5x-6=9xy+5x-10
6)-8ay+7cx +5+3cy+8a=7cx+5+3cy
7)-7+8by-7ay+6+by =9by-7ay-1
8)-5ac + 8 -2by +7az - 3by =7az-5by-5ac+8
9)-8c - 9y +6c +4 + 9y =-2c+4
10)a - 5y (drugich) - 3y(drugich) - 8-6a =8y²-5a-8